EMPIRICAL ANALYSIS OF THE DYNAMICS OF TOURISTS USING A SIMPLE STOCHASTIC MODEL: CASE OF OKINAWA. Issue 2 (29th June 2015) - Iwahashi, Roki; Ito, Tadashi
<x xml:space="preserve">Abstract</x> Unlike the conventional theoretical approach explaining tourism demand by various kinds of determinants, this paper proposes a model in which probabilistic behavior explains the dynamics of the number of tourists. More specifically, the model assumes two different probabilities: one for first‐time travelers and another for frequent travelers. This paper empirically examines the dynamics of tourists to Okinawa, Japan. While income and transport costs explain the probability of first‐time visitors, they do not explain the probability of returning visitors; however, congestion index, which reflects the busy lifestyle of larger cities, does. This suggests that tourism policy should differ depending on how mature or well established a location is as a tourist destination. Given that Okinawa is acknowledged as the foremost resort destination among Japanese, the priority for resource allocation of tourism promotion should focus on the preservation of the natural environment and original culture, thereby offering a unique experience to visitors.